ANALISIS PEMANFAATAN MEDIA PEMBELAJARAN WAYANG KARDUS TERHADAP KREATIVITAS PESERTA DIDIK PADA MATERI PEWAYANGAN KELAS 2 SDN KLECO 1 SURAKARTA - Sabrina, Salsa; Prihastari, Ema Butsi; Mustofa, Mukhlis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning Javanese language in puppetry material in elementary schools still faces various problems, including the use of less innovative learning media and the delivery of material that tends to be monotonous, resulting in low student creativity. This study aims to analyze the use of cardboard puppet learning media in improving student creativity in puppetry material for grade II SDN Kleco 1 Surakarta in the 2025/2026 academic year. This study uses a descriptive qualitative approach with research subjects of grade II B students totaling 28 people and grade II B teachers. Data collection techniques were carried out through observation, interviews, and documentation by applying triangulation of techniques and sources to ensure data validity. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of cardboard puppet learning media has a positive impact on the puppetry learning process. This media is able to improve student creativity, seen from the courage of students in playing the role of wayang characters, telling stories in their own language, as well as increasing activeness and enthusiasm during learning. In addition, cardboard puppet media helps students understand the material more concretely and creates a pleasant learning atmosphere. Cardboard puppets are also easy to make, inexpensive, and environmentally friendly, making them an effective alternative medium for Javanese language learning in lower elementary school grades.